Application of indoline dyes attached with strongly electron-withdrawing carboxylated indan-1, 3-dione analogues linked with a hexylthiophene ring to dye-sensitized solar cells. Issue 27 (5th July 2018) - Matsui, Masaki; Tanaka, Nagisa; Funabiki, Kazumasa; Haishima, Yuki; Manseki, Kazuhiro; Jin, Jiye; Inoue, Yukiko; Higashijima, Shinji; Kubota, Yasuhiro
Abstract: An indoline dye attached with a carboxylated indan-1, 3-dione moiety linked with a hexylthiophene ring exhibited the highest conversion efficiency among six analogues and D205 . This result comes from the bathochromic UV–vis absorption band, suitable energy levels, good stability for redox process, and sufficiently long excited-state lifetime. Graphical abstract: Image 1 Highlights: Indoline dyes showing λ max in the range of 561–821 nm. Best indoline sensitizer among six analogues. Importance of energy levels, fluorescence lifetime, and stability as sensitizers.